Komparasi Literasi Informasi Petani Pengunjung Kebun Percontohan Dan Media Sosial Taman Teknologi Pertanian Pacitan - malik, Rika jayanti; Hariadi, Sunarru Samsi; Martono, Edhi; Witjaksono, Roso (Jurnal KIRANA, 2023)
The study focuses on the comparison of farmers information literacy who had visited the demonstration area and social media of the Pacitans Agricultural Technology Park (TTP). Quantitative method was used to research and purposive sampling was used to select sample in Pacitan district. 167 farmers were selected as the sample form 6 subdistrict. Variable of research are farmers characteristics, the existence of TTP Pacitan, and farmer information literacy for agricultural technology. Non parametric statistical was used to analysis of comparison and correlation. The results showed (1) the farmers characteristic who social media acces younger and more income than farmer who visit to demonstration area ,(2) the existence of TTP Pacitan in the demonstration area is significantly different (0.000 <0.05) than existence on social media. The implementation of the functions of dissemination, extention/training, entrepreneurship development, and making agro-educational-tourism areas in the demontration area is higher than on social media, (3) the information literacy of farmers who visit the garden are significantly different (0.000 <0.05) with farmers who access the social media. Farmers who visit the demonstration area higher information literacy than farmers who visit social media, (4) overall, the farmers age (0.034 <0.05), smartphone ownership (0.001 <0.05), and existence of TTP Pacitan (0.000 <0.05) are related to farmer information literacy. Partially, the existence of TTP Pacitan both demosntration area and social media is related to farmers information literacy. The balance of TTP Pacitan existence in demonstration area and social media can increase farmers information literacy achievements rtoward agricultural technology.